Cultural Shifts in the Use of Acehnese Language in Community Interactions in Banda Aceh City - Lusi Chairun Nisak, Cut; Izzati, Nurul; Ayuning Anjar, Yuva (UIN Sjech M. Djamil Djambek Bukittinggi, 2024)
This study is motivated by the declining number of Acehnese speakers in everyday interactions within the community in Banda Aceh. This research aims to identify the factors influencing the shift in the use of the Acehnese language in daily interactions among the community in Banda Aceh. The analysis in this study employs Herbert Blumer's symbolic interactionism theory and utilizes a qualitative method with a phenomenological approach. Data were collected through observation, in-depth interviews, and documentation. The findings of this study reveal that the shift in the use of the Acehnese language begins within the family environment. A lack of awareness among parents to pass down and instill the use of the Acehnese language in their children leads to a failure in cultural transmission to future generations. In addition to family, the school environment also contributes to the declining use of the Acehnese language, as teaching activities predominantly use Indonesian, with minimal local Acehnese language lessons. Furthermore, the influx of migrants in Banda Aceh who are not proficient in Acehnese also results in the community rarely using the Acehnese language in public, making Indonesian the dominant language used as a collective action to adapt language use to those around them. This study highlights the need to enhance the collective awareness of the community in preserving and maintaining the Acehnese language, as well as the necessity for educational policies that better support the teaching of the Acehnese language in schools.